Do Female and Male Students Perform Differently in Listening Test? - Wahyuni, Emi Nurul; Zamzam, Ahmad; Khotimah, Khusnul (Universitas Islam Negeri Raden Intan Lampung, 2020)
As one of English- proficiency testing methods for non- native speakers, TOEFL is also used as a graduation requirement in almost every university in Indonesia. However, empirical studies report that a considerable number of students performed unsatisfactory. Therefore, many studies have been geared to investigate various aspects of TOEFL related things with the utmost purpose of helping students to meet the expected requirement. This includes scrutinizing gender factors in TOEFL like tests. Basing on quantitative ex-post facto, this research is aimed to see whether gender plays as a contributing factor to students’ ability to answer overview and detailed questions in the TOEFL listening. In this study, 42 out of 94 students’ scores were randomly selected. The data were collected from a TOEFL-like test’s result and were then analyzed using an Independent t-test on SPSS. Based on the t-test analysis, the result showed that there is a different performance of students based on gender, between male and female students which can be seen from the different mean scores between them (male= 10.19 and female =10.19). Nevertheless, the difference was not significant since the t table > t value (2.021>.871). Keywords: detailed and overview question, gender, students’ listening ability, TOEFL-like listening.